The Effectiveness of Digital Marketing in Increasing Sales on E-Commerce in Indonesia (Nomico, 2025)
This study aims to analyze the effectiveness of digital marketing in increasing sales in e-commerce in Indonesia. The background of the study is based on the increasing use of digital marketing strategies by business actors, but not all are able to experience a significant impact on sales results. This study used a descriptive qualitative method with data collection techniques such as in-depth interviews, observation, and documentation with e-commerce business actors, marketing managers, and consumers. Data analysis was conducted using the Miles and Huberman approach through data reduction, data presentation, and drawing conclusions. The results show that digital marketing strategies, specifically social media, SEO/SEM, and influencer marketing, have proven effective in increasing brand awareness and interaction with consumers. Significant sales increases are experienced by business actors who consistently implement these strategies, while MSMEs face obstacles such as limited resources, high advertising costs, and intense competition. Supporting factors for success include content creativity, utilization of analytical data, and direct interaction with consumers. This study confirms that the effectiveness of digital marketing is greatly influenced by the strategy, consistency, and capacity of business actors, as well as the need for ecosystem support for MSMEs to compete sustainably.